UNIVERSITIES IN THE ERA OF INDUSTRY 4.0 AND SOCIETY 5.0: CHALLENGES, STRATEGIES, AND IMPLEMENTATION IN INDONESIA - Supriyantono, Andoyo; Wajo, M. Jen; Widayati, Trisiwi W. (Jurnal Abdisci, 2026)
Abstract: Background. The Introduction to Campus Life for New Students (PKKMB) is an essential program designed to facilitate the transition of freshmen into university life, equipping them with the skills and values required to succeed in higher education. Aims. This article discusses the implementation of PKKMB at the University of Papua, held on August 20–22, 2025, with 1,999 participants across three campuses: Manokwari, Sorong, and Waisai Raja Ampat. In the era of the Industrial Revolution 4.0 and Society 5.0, PKKMB plays a strategic role in preparing students to adapt to rapid technological changes while upholding national values. Methods. The program emphasizes academic readiness, character development, disaster preparedness, and the cultivation of 21st-century skills, including critical thinking, problem-solving, collaboration, communication, and lifelong learning. The opening ceremony was symbolically marked by the Rector of the University of Papua with the pinning of participant badges. Conclusion. The outcomes highlight the importance of strengthening student resilience, national identity, and global competencies to face the challenges of future education and societal demands.